Study of the Customer Behavior in Buying Groceries Online after the Global Pandemic in Nepal - Parajuli, Nancy (Nepalese Journal of Business, 2024)
This study examines customer behavior in buying groceries online after the global pandemic in Nepal. Customer satisfaction/decision is the dependent variable. The independent variables are perceived ease of use, perceived service quality, perceived security, online payment process, trust and interest and consumer purchase behavior. The primary source of data is used to assess the opinions of the respondents regarding customer behavior in buying groceries online after the global pandemic in Nepal. The study is based on primary data from 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and factors affecting customer satisfaction/decision in buying groceries online after the global pandemic in Nepal.The study showed that perceived ease of use has a positive impact on the customer satisfaction/decision. It indicates that ease of use provided by OGS platform leads to the customer satisfaction/decision in OGS. Likewise, perceived service quality has a positive impact on the customer satisfaction/decision. It implies that quality of service provided by OGS platform leads to customer satisfaction/decision in OGS. Similarly, perceived security has a positive impact on the customer satisfaction/decision. It indicates that the security provided by OGS platform would result in customer satisfaction/decision in OGS. Similarly, the online payment process has a positive impact on the customer satisfaction/decision indicating that that good online payment process leads to the customer satisfaction/decision in OGS. Further, trust and interest have positive impact on the customer satisfaction/decision. This indicates that that trust and interest on OGS service provider would result in customer satisfaction/decision in OGS. Furthermore, consumer purchase behavior has a positive impact on the customer satisfaction/decision. This implies that positive consumer purchase behavior leads to customer satisfaction/decision in OGS.